2002
DOI: 10.3727/000000002783985396
|View full text |Cite
|
Sign up to set email alerts
|

The Release of Excitatory Amino Acids, Dopamine, and Potassium following Transplantation of Embryonic Mesencephalic Dopaminergic Grafts to the Rat Striatum, and Their Effects on Dopaminergic Neuronal Survival In Vitro

Abstract: A major limitation to the effectiveness of grafts of fetal ventral mesencephalic tissue for parkinsonism is that about 90-95% of grafted dopaminergic neurones die. In rats, many of the cells are dead within 1 day and most cell death is complete within 1 week. Our previous results suggest that a major cause of this cell death is the release of toxins from the injured CNS tissue surrounding the graft, and that many of these toxins have dissipated within 1 h of inserting the grafting cannula. In the present exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…2002), while other modes of cell death have been addressed less systematically (Cicchetti et al . 2002; Zietlow et al . 2002).…”
mentioning
confidence: 99%
“…2002), while other modes of cell death have been addressed less systematically (Cicchetti et al . 2002; Zietlow et al . 2002).…”
mentioning
confidence: 99%
“…Indeed, previous studies have shown that neuronal survival markedly increased when the injection of dopaminergic cell suspension was delayed for more than one hour following cannula insertion. 160,161 Regulatory T (T REG ) cells play a vital role in maintaining immunological tolerance and homeostasis. 162,163 They are implicated in numerous autoimmune and inflammatory diseases and have been clinically utilized to improve survival rates in various organ transplantations through adoptive transfer after ex vivo expansion.…”
Section: Strategies Targeting Innate Immunitymentioning
confidence: 99%
“…202 This suggests that at the time of implantation, there are factors relating to the traumatic delivery of the cells to the CNS, which compromises the viability and survival of the transplanted dopaminergic cells. Indeed, it is known that at the time of surgery, there is a brief surge of excitatory amino acid (EAA: glutamate and aspartate in this review), dopamine, and potassium, 203 and thus the cell loss during phase 3 may have an excitotoxicity basis. Normally the cytosolic calcium homeostasis is maintained by active mechanisms that store calcium in the mitochondria or power its extrusion out of the plasma membrane.…”
Section: Cell Implantation Factorsmentioning
confidence: 99%
“…207 On the other hand, brief exposure to high-level EAA elicits cytotoxicity on embryonic dopaminergic neurons in vitro, and elevated dopamine and potassium concentrations in the culture medium further enhance the neuronal vulnerability to EAA treatment. 203,[208][209][210] Treatment with NMDA and AMPA receptor antagonists can protect cultured embryonic dopaminergic neurons against oxidative stress and block glutamate-induced neurotoxicity in vitro. 208,211 However, EAA inhibitors have yet to be shown to rescue dopaminergic neurons in embryonic mesencephalic grafts subject to EAA challenge.…”
Section: Cell Implantation Factorsmentioning
confidence: 99%